Foliar trichomes of the evergreen and semi-deciduous species of the genus Quercus (Fagaceae) in the Iberian Peninsula - LLAMAS, F.; PEREZ-MORALES, C.; ACEDO, C.; PENAS, A. (Botanical Journal of the Linnean Society, 1995)
The leaf trichomes of the evergreen and semi-deciduous species of the genus Quercus living in the Iberian Peninsula were studied by means of SEM and LM. The SEM has been particularly useful because of the high quality of the illustrations and the possibility of recognizing the structures under I,M or the stereomicroscope afterwards. The studied species were: Quercus coccifera, Q ilex, Q rotundifolia, Q suber, Q canariensis, Q faginea, Q brateroi and Q lusitanica. All species show some exclusive particularities that permit their identification using these characters. The abaxial surface of the leaf always has more trichomes than the adaxial and hence provides more characters for identification. Quercus alpestris Boiss. shows the same features in the leaf trichomes as Q faginea Lam. A key for identification using these characters is provided.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: key; leaf; LM; SEM